Comparative immune-profiling of three cattle breeds infested with Rhipicephalus microplus and Ixodes ricinus-infested BALB/c mice - Maritz-Olivier, Christine (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.